2018
DOI: 10.1093/biolinnean/bly130
|View full text |Cite
|
Sign up to set email alerts
|

Do differences in bite force and head morphology between a native and an introduced species of anole influence the outcome of species interactions?

Abstract: Species invasions may drive native species to extinction. Yet, the role of competition with a closely related native species in the establishment success of an invasive species remains poorly understood. Indeed, opportunities to study native-invasive competition in action are rare, especially at the very first stages of the invasion. We studied the recent invasion of the lizard Anolis cristatellus in Dominica, where the native Anolis oculatus occurs. We examined the species difference in bite force as a proxy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Anolis oculatus presents species‐specific signals (i.e. display: Dufour et al, 2018a; and morphology: Dufour et al, 2018a; Dufour et al, 2018) and recognition (this study) allowing it to discriminate between conspecifics and A. cristatellus , despite having no common history with the invasive species (Losos, 2009). This result enriches the unexpected, yet significant list of examples of allopatric species who have been demonstrated to show species recognition (Ord, King, & Young, 2011).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Anolis oculatus presents species‐specific signals (i.e. display: Dufour et al, 2018a; and morphology: Dufour et al, 2018a; Dufour et al, 2018) and recognition (this study) allowing it to discriminate between conspecifics and A. cristatellus , despite having no common history with the invasive species (Losos, 2009). This result enriches the unexpected, yet significant list of examples of allopatric species who have been demonstrated to show species recognition (Ord, King, & Young, 2011).…”
Section: Discussionmentioning
confidence: 91%
“…In Panama and Costa Rica, Pasch et al (2013) revealed that aggressive dominance mediates altitudinal zonation in two species of neotropical singing mice. In Dominica, morphological (Dufour et al, 2018a), physiological (Dufour et al, 2018) and behavioural evidence (Dufour et al, 2018b) (Anderson & Grether, 2010;Grether et al, 2017), reproductive (Höbel & Gerhardt, 2003) and exploitative (resource use ;Huber, León, Hendry, Bermingham, & Podos, 2007;Huber & Podos, 2006) competition between closely related species may drive changes in species recognition and display. Indeed, populations can respond to aggressive interspecific interference by shifting phenotypically in traits that affect the rate, intensity or outcome of interspecific aggression (Anderson & Grether, 2010;Grether et al, 2013Grether et al, , 2017Grether, Losin, Anderson, & Okamoto, 2009).…”
Section: F I G U R E 3 Proportion Of Time Spent Displaying (M ± Se) Bymentioning
confidence: 99%
See 2 more Smart Citations
“…Lastly, as invasive species tend to be generalist and highly adaptive species with broad niches [26][27][28], filling seemingly untaken niches would aid invasive success and establishment. Indeed, on Dominica, nocturnally active invasive A. cristatellus, that arrived around 2000 and competes with its native sister species [29,30], are presumed to fill an empty niche given the low number of nocturnally active herpetofauna species [27].…”
mentioning
confidence: 99%